Delegated Legislation in the Peruvian Constitution of 1979: Some Problems and Experiences of the Period 1980-1985 - Eguiguren Praeli, Francisco José (1985)
The paper analyzes how the strengthening of the Executive Branch has allowed the government to assume legislative functions that traditionally corresponded to the Legislative Branch, which has led to an increasingly active presence of the Executive in the field of normative production. In this regard, it is noted that the 1979 Constitution contemplated the delegation of legislative powers to the Executive, but the experience of the 1980s revealed deficiencies in the regulation and supervision of this delegation. The author mentions some examples in which the Executive dictated norms in matters such as organic laws, tax and criminal legislation, arguing that certain areas should be reserved only to the Parliament. Therefore, the paper proposes greater parliamentary control and the need to respect constitutional limits to avoid abuses in the use of these powers.